Polychaete diversity in the Scotia Arc benthic realm: Are polychaetes tracers for faunal exchange? - Montiel San Martin, Americo Manuel; Quiroga, Eduardo; Gerdes, Dieter; Ebbe, Brigitte (My University, 2016)
The Scotia Arc is the only shallow-water and island bridge linking nowadays Patagonia and the Antarctic. The Antarctic Circumpolar Current as an oceanographic peculiarity makes this region an interesting biogeographic transition zone, because this frontal system traditionally is said to isolate the Antarctic fauna from that of the adjacent northern ecosystems. Based on benthos samples from three expeditions onboard R/V Polarstern, we studied distribution patterns of 200 polychaete species and 34 major benthic taxa in order to evaluate the role of polychaetes in the benthic realm of this part of the Southern Ocean. ANOSIM test distinguished three station groups: the central eastern Scotia Sea, the continental shelf off South America and stations at the tip of the Antarctic Peninsula. These station groups differed in organism densities and diversities with stations at the tip of the Antarctic Peninsula hosting the most diverse and dense community. The polychaete diversity patterns in the three assemblages evidenced closer connectivity between the tip of the Antarctic Peninsula and the central eastern Scotia Sea than between the continental shelf off South America with either the stations off the tip of the Peninsula or the central eastern Scotia Sea. This is probably supported by the Polar Front, which divides the island chain into two branches. Species distribution and community patterns of polychaetes appear to be associated with oceanographic and sediment conditions in this region. Most of the shared species showed the capability to tolerate differences in hydrostatic pressure. We suggest that the islands of the Scotia Sea may constitute a bridge for exchange of benthic species, particularly for polychaetes with eurybathic distribution and high dispersal capabilities.
Keywords: macrobenthos; antarctic; magellan; beta diversity; eurybathy